Reproductive and Sexual Health Education in Students with Intellectual Disabilities: A Systematic Review - Jalanidhi, Dayinta Galih; Azizah, Nur (Universitas Negeri Malang, 2022)
This research feeds a systematic review research that aims to find learning methods used by teachers in learning Reproductive Health Education and Sexual in students with intellectual disabilities. Eight articles published between 2013 and 2021 were used in the study. The results of the study describe in learning Reproductive and Sexual Health Education can use training methods and role-playing with learning materials are awareness and prevention of sexual crimes, hygiene, and self-care, escape and recovery from sexual crimes experienced. The conclusion that can be drawn based on this study is the methods used in learning Reproductive and Sexual Health Education are training and role-playing, but teachers must learn the curriculum, norms, and rules, as well as plan the learning programs to be carried out.